The Effectiveness of Group Counseling in Reducing Symptoms of Post-Traumatic Stress Disorder and Improving the Level of Adaptation and Academic Achievement among Syrian Refugee Children in Jordan - Abueita, Siham; Arabiat, Eman (Dirasat: Educational Sciences, 2021)
The current study aims to verify the impact of the effectiveness of a group counseling program according to the dialectical behavioral theory in reducing symptoms of post-traumatic stress disorder, and improving the level of psychological and social adjustment and academic achievement of Syrian refugee children in Jordan. The study members consisted of a convenient sample of (30) Syrian children from the Al-Arakeh Association of the Ministry of Social Development for the year (2017). They were chosen intentionally and were randomly distributed into two groups: an experimental group consisting of (15) children and a control group consisting of (15) children. Three metrics were prepared: post-traumatic stress disorder scale, psychosocial adjustment scale, and Arabic and mathematics achievement tests. A counseling program was prepared according to the dialectical behavioral theory, consisting of (12) sessions, the duration of each of which was one hour; the program was then applied to the experimental group. The results of the study showed that there were statistically significant differences in all dimensions of post-traumatic stress disorder in improving the level of psychosocial adjustment and in improving academic achievement in favor of the experimental group. It showed that there were no statistically significant differences between the post-traumatic and follow-up applications in the areas of post-traumatic stress disorder, in the areas of psychosocial adjustment, and in academic achievement in Arabic and mathematics. The study concluded with several recommendations, including the need to develop effective therapeutic intervention strategies for Syrian refugee children.